Hydrological Model of Upstream Aih Tripe Watershed for Drought and Flood Prediction - . NASRULLAH; BUDI KARTIWA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
The objectives of this research is to analyze biophysic caharacteristics of Upstream Aih Tripe Watershed and to predict discharge characteristic of Aih Tripe River based on hydrological models application. Modified H2U model is applied to predict instantaneous discharge, meanwhile GR4J model is applied to predict daily discharge. Upstream Aih Tripe characteristics are,1,115.2 km2 wide, stretch watershed type (Gravelius index 4.31), equivalent length (L) 252.40 and equivalent width (l) 4.42, parallel drainage pattern, maximum river order is 5 and drainage dencity 1.37 m m-2, global slope index (Ig) 2.0 and specific high different (Hg) 0.06. Instantaneous discharge simulation results at dry season are: instantaneous maximum discharge is 364.8 m3 s-1 and time to peak 4 hours, rainfall maximum intensity is 29 mm hour-1, rainfall is 45.9 mm with duration 5 hours. In rainy season, maximum discharge is 605.2 m3 s-1 and time to peak 2 hours, rainfall maximum intensity is 40.8 mm hour-1, rainfall is 73.2 mm with duration 7 hours. Maximum discharge during El Nino condition is 131.4 m3 s-1 (30 September) and minimum dischargeis 8.2 m3 s-1 (31 March). Discharge simulation during La Nina, maximum discharge is 328.3 m3 s-1 (11 December) and minimum discharge is 8.5 m3 s-1 (5 October).